Canine Tick-Borne Encephalitis: Clinical Features, Survival Rate and Neurological Sequelae: A Retrospective Study of 54 Cases (1999–2016) - Kleeb, Christina; Golini, Lorenzo; Beckmann, Katrin; Torgerson, Paul; Steffen, Frank (Frontiers in Veterinary Science, 2021)
Tick-borne encephalitis (TBE) is one of the most important infectious diseases of the central nervous system in dogs from endemic areas. While in humans survival rate and long-term outcomes are well described, these data are lacking in veterinary literature. The aim of the present paper is to characterize the clinical aspects of TBE and to investigate fatality rate, long term outcome and the long term neurological sequelae in a population of dogs infected with TBEV. We performed a retrospective analysis of 54 dogs diagnosed with TBE at the veterinary hospital of the University of Zurich between 1999 and 2016. Medical data such as signalment, clinical presentation, results of diagnostic procedures, treatment and outcome were collected and analyzed. Statistical analysis including a cox proportional hazard model using a backward stepwise regression approach was performed. In 62% of the TBE cases unspecific signs were described before the onset of neurological signs, resembling a biphasic appearance that is well known in human TBE. Case fatality rate was 33% and all dogs died within the first 4 months after diagnosis. Long term neurological sequalae were detected in 17 % of the TBE cases. For each day of clinical signs before hospital entry the odds of sequalae increased by a factor of 1.88 (CI 1.04-3.15). Older dogs and dogs presented with seizure activity had an increased hazard risk of death (Hazard ration =1.2, p =0.03;and 9.38, p = 0.001 respectively) In conclusion, despite TBE being a life-threatening diseases with severe clinical signs, the survival rate in our study was 67%. However, long term sequalae can be of concern especially in dogs with longer clinical course.